ULASAN HUKUM TENTANG EKONOMI SYARIAH TERKAIT KENAIKAN IURAN ASURANSI KESEHATAN BPJS BAGI PESERTA SELAMA KRISIS EKONOMI - Ari Agung Nugroho; Tehedi Tehedi (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study discusses the legal review of Islamic economics related to the policy of increasing BPJS health insurance contributions for participants during the economic crisis. From an Islamic economics perspective, the formulation of public policy must comply with the principles of justice, benefit, and protection of vulnerable groups, in accordance with the maqashid syariah. The literature review found that the increase in BPJS Health contributions during the crisis, although aimed at covering financial deficits and maintaining programme sustainability, imposes a burden on low-income communities and has the potential to cause harm. In Islamic law, policies that increase economic hardship and are not commensurate with the benefits of services are considered to fall short of the principles of justice and public welfare. Therefore, policy reformulation is necessary to align with Sharia principles, including through optimising subsidies, transparent fund management, and protecting vulnerable participants.